Eighty years of undergraduate education in nutrition in Brazil: An analysis of the 2009-2018 period - das NEVES, Janaina; Borba ZANLOURENSI, Clorine; Martins Álvares DOMENE, Semíramis; BATISTA, Beatriz; de Araújo CALADO, Carmen Lúcia; de Assis Guedes de VASCONCELOS, Francisco (Revista de Nutrição, 2023)
Objective To carry out an analysis of postgraduate education in Nutrition in Brazil in the period 2009-2018, including distance learning. Methods The article presents a historical-documentary analysis of the trajectory of Nutrition courses from 2009 to 2018. The bibliographic survey was carried out in the electronic databases of the Scientifi c Electronic Library Online, the National Library of Medicine, Google Academic databases, and through data collection in government websites and other institutions. Results In December 2018, there were 709 face-to-face and 1,094 distance learning Undergraduate Courses in Nutrition in the country. In the period, there was a 181.5% increase in the number of face-to-face courses, being 195.1% in the private sector, responsible for 89.1% of the total courses in the country. The highest concentration identified was in the Southeast Region did not change substantively in the period. Conclusion With 1,803 undergraduate courses in Nutrition in Brazil, of which the majority is composed of distance learning courses, the current scenario may be the most dramatic in the history of nutrition education in Brazil. Care must be taken to ensure that it is consistent, marked by opportunities for learning in society, in which the student can develop an investigative, critical, innovative spirit, having their professional identities clear in a multidisciplinary work team. The expansion of the offer of undergraduate courses in Nutrition did not correct regional asymmetries.